Linear butene skeletal isomerization over boron-promoted ferrierite - Coronati, Iván (2008)
Boron-promoted potassium-ferrierite catalysts were prepared following the wet impregnation technique. Both boron concentration and pH of impregnating solution were changed. Catalytic behavior was measured during the butene skeletal isomerization. H+ ion exchange induced by impregnation medium and presence of boron species promote catalytic activity, isobutene yield, and catalyst stability. The catalyst impregnated with 0.01 M solution at pH 0.8 showed the best performance. The effect of temperature, butene partial pressure, and contact time was evaluated. The high stability of this catalyst is an important goal. Large conversion and high isobutene yield were reached in the 400-525 °C range; the largest yield (38%) was obtained at 475 °C. Both linear butene conversion and isobutene yield increased by increasing contact time or by decreasing the butene partial pressure. Isobutene yield remained practically constant during 24 h of reaction. Carbonaceous deposit formed during reaction was characterized by temperature-programmed oxidation and by FTIR. Coke amount at different reaction conditions was lower than 0.7%. Active catalysts displayed the maximum of the combustion peak between 560 and 608 °C, shifting to higher temperature when reaction temperature increases. After 24 h of reaction at 450 °C, the carbonaceous deposit only reaches 0.9%, being it 6.0% after 120 h.